Lifestyle Intervention Improves Heart Rate Recovery from Exercise in Adults with Type 2 Diabetes: Results from the Look AHEAD Study - Paul M. Ribisl; Sarah A. Gaussoin; Wei Lang; Judy Bahnson; Stephanie A. Connelly; Edward S. Horton; John M. Jakicic; Tina Killean; Dalane W. Kitzman; William C. Knowler; Kerry J. Stewart; Look AHEAD Research Group (Journal of Obesity)
The primary aims of this paper were (1) to evaluate the influence of intensive lifestyle weight loss and exercise intervention (ILI) compared with diabetes support and education (DSE) upon Heart Rate Recovery (HRR) from graded exercise testing (GXT) and (2) to determine the independent and combined effects of weight loss and fitness changes upon HRR. In 4503 participants (45–76 years) who completed 1 year of intervention, HRR was measured after a submaximal GXT to compare the influence of (ILI) with (DSE) upon HRR. Participants assigned to ILI lost an average 8.6% of their initial weight versus 0.7% in DSE group (P<0.001) while mean fitness increased in ILI by 20.9% versus 5.8% in DSE (P<0.001). At Year 1, all exercise and HRR variables in ILI improved (P<0.0001) versus DSE: heart rate (HR) at rest was lower (72.8±11.4 versus 77.7±11.7 b/min), HR range was greater (57.7±12.1 versus 53.1±12.4 b/min), HR at 2 minutes was lower (89.3±21.8 versus 93.0±12.1 b/min), and HRR was greater (41.25±22.0 versus 37.8±12.5 b/min). Weight loss and fitness gain produced significant separate and independent improvements in HRR.